A comparative analysis of experts' and consumers' perceptions of regionality in Australian wine purchase decisions. (3rd July 2017) - Nallaperuma, Kaushalya; Bandyopadhyay, Argho; Lockshin, Larry
ABSTRACT: This study provides insight into consumers' perception of regionality when purchasing regional wine in terms of regional specialisation for style, volume of production of the wine style, quality of the wine, heritage of the wine region and the distinctiveness of the wine styles produced in the wine regions of Australia. Data were collected from 203 Australian wine consumers through an online survey. The study compares the results of this study with Easingwood et al. [2011. The drivers of wine regionality. Journal of Wine Research, 22 (1), 19–33.] study on experts' opinion of regionality drivers. This paper will expand knowledge on how consumer involvement levels impact decisions relating to purchasing regional wine. This study is of value to academics and wine practitioners alike. It contributes to the wine literature by providing a new perspective on consumers' perception and draws attention to the risk of drawing conclusions about wine consumption based on experts' opinions as being reflective of the average consumers' purchase decision-making.